Knowledge, attitude and reported practice of primary school teachers on specified school health activities in Danuphyu Township, Ayeyarwaddy Region, Myanmar - Htun, Ye Minn; Lwin, Kay Thi; Oo, Nwe Nwe; Soe, Kyaw; Sein, Than Tun (South East Asia Journal of Public Health, 2014)
Schools are important settings for comprehensive health promotion. School exerts the most influence on the lives of children and youth. Schools can play a key role in supporting students health and, by extension, the health of their families and communities. This school-based cross sectional descriptive study was conducted in Danuphyu Town-ship from June to November, 2012. This study aimed to identify the levels of knowledge, attitude and practice of primary school teachers concerning four school health activities: comprehensive school health education; healthy school environments; prevention and control of communicable diseases; and nutritional promotion and food safety. The sample consisted of 97 teachers from 23 primary schools were randomly selected to participate in the study. A pre-tested structured questionnaire was used as a data collection tool. It was found that 62.9% of teachers achieved a high level of knowledge scores (mean knowledge score of 39.10 with SD 3.087); 57.7% had a positive attitude towards school health activities; 52.6% of teachers achieved high reported practice scores (with mean practice score of 66.07 and SD 4.17); teachers from urban areas, over 50 years of age, and with service duration of 20-24 years, are statistically significantly associated with higher levels of reported practice; teachers with high knowledge and posi-tive attitude scores achieved higher reported practice scores, but these associations are not statistically significant. Overall, over 50% of the teachers had a high knowledge, a positive attitude and high practice scores relating to school health activities, and this shows that favorable conditions exist at the schools among the teachers for further strengthening the school health program of Myanmar. Enhancing teachers' involvement in school health activities would establish good outcomes of the school health promotion program. Provision of continuous training of teach-ers in school health would further enhance knowledge of teachers, and would gradually inculcate positive attitudes among them. This would lead towards more involvement of teachers in school health activities. South East Asia Journal of Public Health 2013; 3(1): 24-29 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17707